The Art and Craft of Bricolage in Evaluation - Aston, Thomas; Apgar, Marina (Institute of Development Studies, 2022)
This CDI Practice Paper by Tom Aston and Marina Apgar makes the case f or ‘bricolage’ in complexity-aware and qualitative evaluation methods. It provides a framework based on a review of 33 methods to support ev aluators to be more intentional about bricolage and to combine the com ponent parts of relevant methods more effectively. It discusses two ca ses from practice to illustrate the value added of taking a more inten tional approach. It further argues that navigating different forms of power is a critical skill for bricolage, and that doing so can help to ensure rigour.